2021
DOI: 10.3390/biom11111581
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal Syndrome: New Pathways and Novel Biomarkers

Abstract: Cardiorenal syndrome (CRS) is a multi-organ disease characterized by the complex interaction between heart and kidney during acute or chronic injury. The pathogenesis of CRS involves metabolic, hemodynamic, neurohormonal, and inflammatory mechanisms, and atherosclerotic degeneration. In the process of better understanding the bi-directional pathophysiological aspects of CRS, the need to find precise and easy-to-use markers has also evolved. Based on the new pathophysiological standpoints and an overall vision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 89 publications
(85 reference statements)
0
24
0
Order By: Relevance
“…POSTN was further significantly correlated with LVEF (R = 0.54, P < 0.05, Figure 5I ) and BUN (R = 0.41, P < 0.05, Figure 5J ), while no significant association was observed between POSTN and Scr (R = 0.33, P = 0.16, Figure 5K ), NT-proBNP (R = 0.43, P = 0.063, Figure 5L ), and UA (R = 0.35, P = 0.13, Figure 5M ). The association of CRS with LVEF [ 30 ], NTproBNP [ 31 ], Scr [ 32 ], and BUN [ 33 ] has been verified in multiple studies, which strengthens the reliability of FN1 and POSTN.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…POSTN was further significantly correlated with LVEF (R = 0.54, P < 0.05, Figure 5I ) and BUN (R = 0.41, P < 0.05, Figure 5J ), while no significant association was observed between POSTN and Scr (R = 0.33, P = 0.16, Figure 5K ), NT-proBNP (R = 0.43, P = 0.063, Figure 5L ), and UA (R = 0.35, P = 0.13, Figure 5M ). The association of CRS with LVEF [ 30 ], NTproBNP [ 31 ], Scr [ 32 ], and BUN [ 33 ] has been verified in multiple studies, which strengthens the reliability of FN1 and POSTN.…”
Section: Resultsmentioning
confidence: 92%
“…The advancement and popularization of gene sequencing technology has provided an opportunity to further elucidate the pathological processes of this disease. Recently, many novel biomarkers associated with CRS have been reported, including cystatin 3, galectin 3, NGAL, and KIM1 [ 31 , 41 ]. These biomarkers not only provide the clinical guidelines for CRS diagnosis and prognosis, but also suggest the underlying cut-in points for mechanistic studies.…”
Section: Discussionmentioning
confidence: 99%
“…4 Until recently, there have been few studies on the risk factors of and prediction methods for the short-term prognosis of CRS1. 5 The goal of this study was to explore the risk factors that affect the short-term prognosis of CRS1 in AMI patients and to understand the predictive value of three scoring methods-Sequential Organ Failure Assessment (SOFA), Acute Physiology and Chronic Health Evaluation (APACHE) II, and Simplified Acute Physiology Scores (SAPS) II-on the mortality of AMI patients with CRS1 within 28 days after the onset of AMI, in order to provide clinical guidance.…”
Section: Introductionmentioning
confidence: 99%
“…The recent meta-analysis have demonstrated that CKD deterioration is related to alteration of bone and mineral metabolism as novel risk factors emerged for cardiovascular disease mortality in patients with CKD and CRenal. This relationship is explained by strongly linked with hyperphosphatemia and vascular calcification [ 8 ]. The RAAS play a central factor contributing to end-stage kidney disease (ESKD), particularly in black individuals [ 9 ].…”
Section: Introductionmentioning
confidence: 99%